Evaluation of Minimum Service Standards for River Transportation on Ships on the Mintin – Anjir Sampit Route, Pulang Pisau Regency, Central Kalimantan Province - Alam, Kodrat; Pusriansyah, Ferdinand (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2023)
Mintin Pier located in Pulang Pisau regency of Central Kalimantan province serves the route between Mintin - Anjir Sampit and has 3 ships operating namely the Palapa Agung Ship, Kf Perintis and Maju Bersama. In the operation of river and lake transportation, service standards have a very important value for service users. However, in field conditions there are still some service indicators that are not in accordance with certainty. Based on these conditions, the author conducted a survey of the services and facilities on the ship. The purpose of this study is to determine the conformity of the minimum service standards in the Regulation of the Minister of Transportation Number 61 of 2021 concerning the Implementation of River and Lake Transportation with existing conditions and what services / facilities need to be improved to comply with the established standards. Based on the results of analysts, it is obtained that the ships operating are not in accordance with the Minimum Service Standards in the Regulation of the Minister of Transportation Number 61 of 2021. The authorized ship manager must improve passenger services in accordance with the Regulation of the Minister of Transportation Number 61 of 2021 concerning the implementation of river and lake transportation. Suggestions for improvement for ship managers are as follows: There is a need for additional evacuation route guidance facilities. Adult and child life jackets, fire extinguishers, communication radios, first aid kits in accidents, garbage boxes, smoking prohibition stickers, Navigation lights, There is a need for additional light intensity on the ship. In the need for travel information and travel and security interference information, the Ship must provide a platform connection to the ship and priority access for people with disabilities or the elderly.